Strengthening or weakening? A Study of the Impact of the Responsibility Attribution Framework of Media Depression Coverage on Public Stigma of Depression - Zhao, Xinru; Pan, Jiabao (The Journal of Medicine, Humanity and Media, 2025)
Depression is a common mental health disorder in today’s society, not only affecting many sufferers and their families, but also bringing a heavy burden of illness to society. Public stigma, as an important reason preventing depressed patients from seeking professional help, has become an urgent issue. The media, as an important channel for communicating health information, plays an important role in shaping the public’s perception of depression as a disease in terms of its content as well as the way it is reported. In this context, this study focuses on the impact of attributional framing of responsibility for depression in media reports on public stigma. Specifically, this study utilized an experimental approach to explore how different attributional frames of responsibility (personal, familial, social, and biological) in reporting acted on three core dimensions of public stigma of depression: one-sided attributional perceptions, negative emotional responses, and social distance. It was found that different attributional frames of responsibility in media reports had an impact on public perceptions, and in particular, biological attribution reports weakened public stigmatization of individuals with depression. Further analyses found that the way individuals attribute depression not only affects their emotional responses to patients, but also that emotional responses act as mediators to further influence their social distance to patients. The findings of this study emphasize the importance of attributional framing of media responsibility for stigmatized illnesses in shaping public health perceptions and promoting social support and understanding.